2022
DOI: 10.1111/1745-9133.12611
|View full text |Cite
|
Sign up to set email alerts
|

The sexual recidivism drop in Canada: A meta‐analysis of sex offender recidivism rates over an 80‐year period

Abstract: Research summary In the past, the Canadian government followed in the footsteps of its American counterpart by enacting “sex offender laws.” Since the 1990s, however, the Canadian criminal justice system has taken a different approach to the issue of sex offender recidivism (SOR), focusing on treatment, rehabilitation, and community risk management. This evidence‐based approach has been criticized for not doing enough to prevent convicted offenders from sexually reoffending. This criticism has not been address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 148 publications
0
6
0
Order By: Relevance
“…A meta-analysis allows for the pooling of findings from various studies while accounting for the sample size of each, which is critical in this field of research given the number of small-scale studies based on highly specific samples. The use of a meta-analysis to summarize the likelihood of reoffending among YSOs aligns with prior research on justice-involved adolescents (e.g., Caldwell, 2010, 2016; McCann & Lussier, 2008), as well as research on women (e.g., Cortoni et al, 2010), and adults (e.g., Fazel & Wolf, 2015; Katsiyannis et al, 2018; Lussier et al, 2022). Using a meta-analysis for systematically combining general, violent, and sexual recidivism rates across studies, we revisit Caldwell’s (2016) conclusion that the sexual but not general recidivism of YSOs has been declining over time.…”
Section: Aim Of the Studymentioning
confidence: 70%
See 4 more Smart Citations
“…A meta-analysis allows for the pooling of findings from various studies while accounting for the sample size of each, which is critical in this field of research given the number of small-scale studies based on highly specific samples. The use of a meta-analysis to summarize the likelihood of reoffending among YSOs aligns with prior research on justice-involved adolescents (e.g., Caldwell, 2010, 2016; McCann & Lussier, 2008), as well as research on women (e.g., Cortoni et al, 2010), and adults (e.g., Fazel & Wolf, 2015; Katsiyannis et al, 2018; Lussier et al, 2022). Using a meta-analysis for systematically combining general, violent, and sexual recidivism rates across studies, we revisit Caldwell’s (2016) conclusion that the sexual but not general recidivism of YSOs has been declining over time.…”
Section: Aim Of the Studymentioning
confidence: 70%
“…This meta-analysis suggests that researchers tend to rely on older, secondary data to examine recidivism rates, which might be convenient for academic purposes, but does very little to help monitor the evolution of recidivism rates over time and across jurisdictions. Periods effects on sexual recidivism have been detected for Canadian studies composed mainly of adult perpetrators, but the factors responsible for the observed drop remain elusive (Lussier et al, 2022). The particularities of the youth justice system, the legal context, its culture and practices (e.g., diversion program, treatment) across states/provinces, countries and regions might have confounded our findings for adolescent perpetrators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations